Morphological processes of neologisms in social media - Shahlee, Shakina (2021)
Morphology is a study of word formation and coinage. The advancement of technology through the Internet has led to evolution of English vocabulary as the Lingua Franca of it. This research report investigates the morphological processes used in forming neologisms through selected social media platforms namely, Facebook, Instagram and Twitter. The morphological processes notions adopted in this study are based on several researchers; Murray‟s (1995); Kemmer‟s (2003); Plag (2003). The lists of word formation processes used are acronym, affixation, antonomasia, abbreviation, borrowing, blending, clipping, compounding, conversion, reduplication and onomatopoeia. 93 neologisms were collected throughout the timeframe applied from November 2019 until March 2020. This study is a textual based analysis through qualitative approach. The samples were collected by random sampling of selecting social media influencers within the digital mediated communication as the neologisms analysed under study evolved in a wide platform due to online social media. The aspect of morphological process and word classes of the neologisms were analysed according to the adopted theory mentioned. The result is used to determine the most common morphology applied on the neologisms. The results indicate that acronym is the most common used of new word formation and most new words are formed in noun class through social media in this era. New word formation was found in this study as the sequence formation of words was undefined. This paper concludes that language is evolving occasionally and it is significant to language users by increasing their awareness of the productivity of existing words in the English vocabulary.